1994
DOI: 10.5271/sjweh.1395
|View full text |Cite
|
Sign up to set email alerts
|

Noise exposure, noise annoyance, use of hearing protection devices and distress among blue-collar workers.

Abstract: Green, MD1.2 MELAMED S, RABINOWITZ S, GREEN MS. Noise exposure, noise annoyance, use of hearing protection devices and distress among blue-collar workers. Scand J Work Environ Health 1994;20: 294-300.OBJECTIVES -This study tested the hypotheses that, in high noise levels [~85 dB(A)], hearing protection devices are used largely by workers sensitive to noise, as reflected by reports of noise annoyance, and that the usage would reduce distress symptoms. METHODS -Data collected from 1587 healthy male blue-collar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 25 publications
2
22
0
1
Order By: Relevance
“…Chavalitsakulchai (1989) found that only 20% of the workers used HPDs in the presence of high noise. Other studies also found low compliance (30% to 50%) in HPD use (Abel, 1985;Lusk, 1995;Melamed, 1994). In this study, continuous HPD use showed a clear preservative effect, as reflected by the significantly lower prevalence of hearing loss in the continuous HPD users.…”
Section: Discussionsupporting
confidence: 52%
“…Chavalitsakulchai (1989) found that only 20% of the workers used HPDs in the presence of high noise. Other studies also found low compliance (30% to 50%) in HPD use (Abel, 1985;Lusk, 1995;Melamed, 1994). In this study, continuous HPD use showed a clear preservative effect, as reflected by the significantly lower prevalence of hearing loss in the continuous HPD users.…”
Section: Discussionsupporting
confidence: 52%
“…Melarned et a1 (1994) in a study on 2497 male blue collar workers reported 42.6% (150 out of 352) HPD use in those exposed to noise levels greater than or equal to 85 &(A). Multiple logistic regression analysis indicated that HPD use related not only to exposure level (OR 2.94,95% CI 2.58-3.3), but even more so to high noise annoyance (OR 3.03, 95% CI 2.77-3.29) (Melamed et al, 1994).…”
Section: Hpd Use In Two Millsmentioning
confidence: 99%
“…That is, service-users within mental healthcare institutions may be vulnerable from the outset, since (a) they are often unable to escape from the noise, especially if they are detained under the Mental Health Act or do not have alternative accommodation (b) noise sensitivity may be a predisposing factor for mental illness (Tarnopolsky et al, 1978;Jones et al, 1981) and (c) there exists a demonstrable correlation between noise (its effects and manifestations) and the psychopathology of the individual affected (Jones et al, 1981;Arguelles et al, 1970;Westman and Walters, 1981;Melamed et al, 1994;Belojevic et al, 2001), eliciting greater 'stress' or arousal responses in those with psychological or psychiatric problems.…”
Section: Implications For Hospital Inhabitants -Service Users and Staffmentioning
confidence: 99%